Papa Gregorio Magno e la Simoniaca haeresis - Rizzo, Roberta (Augustinianum, 2013)
Pope Gregory the Great’s homilies and letters document his fight against simony, widely spread among all patriarchates, where sacraments, first of all Holy Orders, were sold, and where one could become a bishop solely through the donations and support of influential people. The Pope asked both laity and bishops to help in eradicating this terrible plague which he considered a real heresy, inasmuch as it debased the dignity of the priesthood and the action of Holy Spirit and undermined the unity of the Church. In an eschatological perspective he invited bishops and laity to cooperate in his reform of ecclesiastical custom according to the Holy Scriptures, the tradition of the Church Fathers and canon law.